New Developments in Multiple Objective and Goal Programming - Jones, Dylan; Tamiz, Mehrdad; Ries, Jana.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume shows the state-of-the-art in both theoretical development and application of multiple objective and goal programming. Applications from the fields of supply chain management, financial portfolio selection, financial risk management, insurance, medical imaging, sustainability, nurse scheduling, project management, water resource management, and the interface with data envelopment analysis give a good reflection of current usage. A pleasing variety of techniques are used including models with fuzzy, group-decision, stochastic, interactive, and binary aspects. Additionally, two papers from the upcoming area of multi-objective evolutionary algorithms are included. The book is based on the papers of the 8th International Conference on Multi-Objective and Goal Programming (MOPGP08) which was held in Portsmouth, UK, in September 2008.
Multi-Objective Stochastic Programming Approaches for Supply Chain Management -- A Review of Goal Programming for Portfolio Selection -- A Hypervolume-Based Optimizer for High-Dimensional Objective Spaces -- Minimizing Vector Risk Measures -- Multicriteria Programming Approach to Development Project Design with an Output Goal and a Sustainability Goal -- Automated Aggregation and Omission of Objectives for Tackling Many-Objective Problems -- Trade-Off Analysis in Discrete Decision Making Problems Under Risk -- Interactive Multiobjective Optimization for 3D HDR Brachytherapy Applying IND-NIMBUS -- Multicriteria Ranking Using Weights Which Minimize the Score Range -- In Search of a European Paper Industry Ranking in Terms of Sustainability by Using Binary Goal Programming -- Nurse Scheduling by Fuzzy Goal Programming.
Keywords: Economics; Artificial intelligence; Mathematical optimization; Operations research; Business logistics; Economics/Management Science; Operations Research/Decision Theory; Optimization; Production/Logistics.; Operations Research, Mathematical Programming; Artificial Intelligence (incl. Robotics).